Use of Non-Prescription Remedies by Ghanaian Human Immunodeficiency Virus-Positive Persons on Antiretroviral Therapy - Amos K. Laar; Awewura Kwara; Priscillia A. Nortey; Augustine K. Ankomah; Michael P. K. Okyerefo; Margaret Y. Lartey (Frontiers Media S.A., 2017)
BackgroundInappropriate use of non-prescription remedies by persons living with human immunodeficiency virus (PLHIV) may result in adverse events or potentiate non-adherence to prescribed medications. This study investigated the use of non-prescription remedies among PLHIV receiving antiretroviral therapy (ART) from four treatment centers in southern Ghana.MethodsA mixed method design using quantitative and qualitative methods was used. This article focuses on the quantitative survey of 540 respondents. Univariate analysis was used to generate descriptive tabulations of key variables. Bivariate analysis and logistic regression modeling, respectively, produced unadjusted and adjusted associations between background attributes of PLHIV and the use of non-prescription remedies. A p-value of < 0.05 was considered statistically significant. All analyses were performed using IBM SPSS Statistics for Windows, Version 20.0.ResultsOne out of three respondents reported the use of non-prescription remedies at least once within 3 months of the survey. Most of these were locally made and included "Angel natural bitters, concoctions from the Christian prayer centers, garlic, and mahogany syrups." These remedies were used concomitantly with antiretroviral medications (ARVs)-46% or administered with ARVs but at different times during the day (43%). Some of the remedies were reportedly prescribed by health workers, or self-initiated during periods of ARVs shortage. Others took them based on their perception of their efficacy. Bivariate level analysis identified ART clinic site, place of residence, and ARV adherence monitoring to be significantly associated with the use of non-prescription remedies (p < 0.05). Multiple logistic regression analysis controlling for covariates confirmed the location of ART clinic as the only predictor of the use of non-prescription remedies. Compared to clients at the large urban teaching hospital (Korle-Bu Fevers Unit ART center), those at the district level (Atua ART center) were ninefold more likely to use non-prescription remedies [adjusted odds ratio (AOR) = 8.84; 95% confidence interval (CI) 2.83-33.72]. Those from a district level mission hospital (St. Martin's ART center) were threefold as likely to use these remedies (AOR = 2.610; 95% CI 1.074-9.120).ConclusionThe use of non-prescription remedies by PLHIV on ART is common in southern Ghana. Usage is mostly self-initiated because of perceived efficacy of remedy, and was more common among clients attending rural ART clinics.